The influence of lime application on the chemical and physical characteristics of acidic grassland soils with impeded drainage. (11th April 2021) - Corbett, D.; Wall, D. P.; Lynch, M. B.; Tuohy, P.
Abstract: Soil acidity and poor nutrient use efficiency are major limiting factors as regards output potential on heavy soils, soils which are dominated by high proportions of clay and organic matter, with impeded drainage, high buffering capacity and located in high rainfall areas. Lime is applied in order to counteract these limiting factors and in turn improve agricultural output and productivity. The current study investigates the effects of two commonly used lime products at three comparable treatment rates, ground lime (7.5, 5 and 2.5 tonne/ha) and granulated lime (7.5, 2.5 and 1.5 tonne/ha), applied across three distinct sites. The ability of each lime product and treatment rate to counteract soil acidity, increase nutrient availability and influence soil physical structure was assessed over time. On average across sites, 1 tonne/ha of each lime product increased soil pH by 0.15 and 0.21 pH units between ground and granulated lime, respectively. Site 3 experienced the greatest increase change in soil pH in comparison to the other two sites, largely due to lower clay content and cation exchange capacity. Granulated lime was 5.7 times more expensive than ground lime in its ability to reduce soil acidity. The high treatment rate showed the greatest reduction in soil acidity, aluminium and iron concentration as a mean across all sites. Morgan's soil test phosphorus concentration increased across all sites, with treatment rates having no effect on the rate of increase. There was evidence of reduced soil compaction and lime application showed no negative implication on soil physical structure.